Activity demands and technical proficiency within the female Australian Rules Football talent pathway - Jennings, J.; Dower, H.; Palmer, J.; Kingsley, M. (International Journal of Sports Science & Coaching, 2025)
The aim of this study was to compare activity and technical demands of match-play at various levels of competition in female elite-junior Australian Football talent pathways. A retrospective, observational design was used. Global positioning system and technical involvement data were collected from 18 Under 19 Coates Talent League (CTL: n = 684), 10 Under 16 National Championships (U16NC: n = 257) and eight Under 18 National Championships (U18NC: n = 171) teams during 120 matches in the 2023 playing season. Total distance (TD) is lower at U16NC level than CTL and U18NC competitions (small effects). Relative distance (RD) and high-speed running (HSR) distance were different with age, and playing level, with CTL and U16NC demands lower than U18NC (small-moderate effects). The total number of technical involvements in U16NC and U18NC were comparable, but generally higher than CTL. Disposal efficiency was the best technical differentiator between playing levels, with both CTL and U16NC (small effects) being significantly lower than U18NC competition. Findings suggest that demands differ as players progress through the talent pathway. The increase in technical efficiency is likely a contributor to the increase in activity demands. Coaches at all levels of the female talent pathway should be aware of match-play demands to effectively prepare players for current and future competition. Technical efficiency seems to be a key differentiator for higher level selection, particularly the ability to dispose of the football effectively. This should be a coaching priority within the talent pathway.